PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Jurnal Proaksi, 2022)
Every company that has gone public is required to submit financial reports that are prepared based on standards and have been audited in a timely manner. ready as per norms and reviewed on time. Truth be told, each year there are as yet numerous public organizations that are late in presenting their yearly monetary reports. This study plans to decide the impact of benefit and firm size on the practicality of monetary revealing with review assessment as a directing variable with a 5-year research period, 2016-2020. The examination was led utilizing quantitative techniques and exploration tests were taken by purposive inspecting strategy in food and drink area organizations. This study utilizes 70 yearly report information of organizations recorded on the Indonesia Stock Exchange. The analysis technique and hypothesis testing used in this research is to use Partial Least Square (PLS) with the help of WarpPLS 7.0 software.Keywords: profitability, company size, timeliness.